HISTORICAL TOURISM WORK LEARNING MODEL AS AN EFFORT TO IMPROVE STUDENTS' LEARNING MOTIVATION IN HISTORY SUBJECTS IN SMA NEGERI 7 GORONTALO - Liputo, Sriwahyuni; Yunus, Resmiyati; Manay, Helman (CV. Fahr Publishing, 2025)
This study aims to apply the historical field trip learning model as an effort to increase student learning motivation in history subjects at SMA Negeri 7 Gorontalo. This study uses a qualitative method using a descriptive approach that describes the historical field trip learning model as an effort to increase student learning motivation in history subjects at SMA Negeri 7 Gorontalo. The data obtained in this study through primary data sources, namely interviews with history subject teachers and students. While secondary data was obtained from reference books, journals, and other relevant information. Data collection techniques include observation, interviews and documentation. The results of this study can be concluded that: during the pre-cycle, students in history learning are less motivated due to several factors, namely a teacher in using a less effective learning model, students who are only busy going in and out of class and some even sleep in class, and from the results of observations that researchers obtained in the field, the percentage of students who are less motivated is 56%, in history learning. Based on the results obtained, researchers use the historical field trip learning model to increase student motivation in history learning. The historical tour was held on Thursday, September 19, 2024. After the action, students who were motivated in learning history reached 87%. Thus, the historical tour learning model in history subjects can increase students' learning motivation.